Heterostructured bulk aluminum with controllable gradient structure: Fabrication strategy and deformation mechanisms. (15th April 2021) - Wang, Ge; Ouyang, Heng; Su, Yishi; Guo, Qiang; Xiong, Ding-Bang; Zhuang, Qianduo; Yue, Zhenming; Li, Zan; Zhang, Di
Graphical abstract: Image, graphical abstract Abstract: We explore the deformation features and mechanisms of bulk gradient aluminum. A powderassembly approach was employed, for the first time, to fabricate bulk aluminum with finelytuned gradient cycles. We found that the deformation behaviors of individual components areaffected by the gradient structure, which is attributed to the hetero-deformation inducedinternal stress. Our experimental and modelling results further reveal that the hardening ofeach component is gradient magnitude dependent, and is governed by the distribution ofgeometrically necessary dislocations. Our work provides new insights into the understandingand development of gradient metals with superior properties.